Luis Ramiro Beltrán: El apocalipsis de la humanidad en El cofre de Selenio - Muñoz, Willy O. (Latin American Theatre Review, 2004)
This article studies El cofre de Selenio, a postmodern play by the Bolivian playwright Luis Ramiro Beltrán. The play is an allegorical search for the light, for the meaning of life, but it is also a discourse for world peace, a statement that denounces the hegemonic ideologies that have oppressed men throughout history, a rejection of the war technology, of the sciences that make possible an apocalyptic nuclear hecatomb. An intercultural plurality contributes to the universality of its aim, however, the referents, though fragmented and plural, they are localized and historically specific. The play itself does not have a plot, in the conventional sense of the term, but the events take place in a synchronic time, in a multispatial place, where thirty-two characters from throughout history interact. (WOM, in Spanish)